A Doomed Technology? On Gene Editing in Bavarian Livestock Agriculture, Policy Field Conflicts and Responsible Research and Innovation - Müller, Ruth; Feiler, Julia; Clare, Amy (Frontiers in Political Science, 2022)
The emergence of CRISPR-Cas9 has recently, for the first time, rendered the large-scale genetic modification of livestock animals such as cows, pigs, and chickens possible. Novel editing targets range from genes that curb disease vulnerabilities, increase muscle mass, or convey hornlessness, to the development of transgenic pigs for medical use. In this article, we discuss the efforts of a transdisciplinary research consortium in Bavaria, Germany, to test the technical and social feasibility of using CRISPR-Cas9-based gene editing as a novel technology in Bavarian small- to medium-scale livestock agriculture. The consortium comprised life scientists, local breeding associations, legal scholars, and social scientists from Science & Technology Studies (STS) and aimed to promote Responsible Research and Innovation (RRI) for gene editing technologies. Research focused on gene editing applications that improved animal health and all editing targets were co-developed with local breeding associations to meet the situated needs of small- to medium-scale livestock farmers in Bavaria. In this article, we discuss why the agricultural stakeholders in the project, that is, the representatives of local breeding associations, considered that, despite the project's success in generating positive research outcomes, it would be unlikely that results will be implemented in Bavarian livestock agriculture. We describe this situation in terms of a tension between agendas in the science and technology policy field and in the agricultural policy field in Bavaria that impacts local farmers' ability to adopt gene editing technologies. We further discuss what it might mean for RRI practices if public stakeholders are unlikely to benefit from the outcomes of RRI practices due to policy field conflicts or other contextual constraints and how STS scholars and other social scientists involved in RRI projects could adjust their practices to possibly redistribute benefits.